Theoretical and experimental investigations of the Landau-Pomeranchuk-Migdal effect in amorphous and crystalline matter - Shul'ga, N.F.; Fomin, S.P. (Вопросы атомной науки и техники, 2003)
The brief review of theoretical investigations carried out in NSC KIPT on the problem of multiple scattering effect on radiation of high energy particles in matter is presented. The comparison of results of the theory with experimental data obtained recently on accelerators of SLAC and CERN at the study of the Landau-Pomeranchuk-Migdal effect in amorphous and crystalline matter is carried out. Дано стислий огляд теоретичних досліджень з проблеми впливу багатократного розсіяння на випромінювання частинок високих енергій у речовині, які виконувалися в ННЦ ХФТІ. Проведено порівняння результатів теорії з експериментальними даними, отриманими нещодавно на прискорювачах SLAC і CERN при дослідженні ефекту Ландау-Померанчука-Мигдала в аморфних і кристалічних середовищах. Дан краткий обзор теоретических исследований по проблеме влияния многократного рассеяния на излучение частиц высоких энергий в веществе, выполненных в ННЦ ХФТИ. Проведено сравнение результатов теории с экспериментальными данными, полученными недавно на ускорителях SLAC и CERN при исследовании эффекта Ландау-Померанчука-Мигдала в аморфных и кристаллических средах.